Jejak Akulturasi Dalam Atap Joglo: Eksplorasi Gaya Arsitektur Jawa Dan Timur Tengah Pada Bangunan Masjid Lawangsongo Ponpes Lirboyo Kota Kediri - Aulia Ananta Habibi; Muhammad Syifa’ Nuqoba (Imajinasi : Jurnal Ilmu Pengetahuan, Seni, dan Teknologi, 2024)
The Lirboyo islamic boarding school in the city of kediri, east java, is one of the islamic boarding schools that proiritizes the salaf method education system (yellow book recitation), a part from being know for its traditional learing methods, the islamic boarding school builiding is also not far from the local architectural approach, varied with middle eastern architecture which creates its own sacred value. One of the building with the javanese architectural approach with a combination of middle eastern architecture is the lawangsongo mosque building. Mosque is a used for large activities organized by the lirboyo islamic boarding school. With a combination of javanese arcitecture and middle eastern architecture, the lawangsongo mosque building is one of the interisting icon in the cottage. The roof is one of the characteristic of the sacred javanese architectural approach and is added to the mihrab, thus creating sacred and religious values in the mosque.